Teacher supervision in educational policy and practice: Perspectives from the External Evaluation of Schools in Portugal - Seabra, Filipa; Mouraz, Ana; Henriques, Susana; Abelha, Marta (Education Policy Analysis Archives, 2021)
The External Evaluation of Schools (EES) has been recognized in Portugal as an important mechanism for producing change in non-higher education schools, even though those changes appear not always to affect the core of educational action – the classroom. Currently in its 3rd cycle of implementation, EES privileges a focus on processes, specifically teaching processes. That justifies our intention to look intently into how processes oriented towards the improvement of teaching practices, such as teacher supervision, are conceptualized in the referentials that guide EES and on the evaluation reports it produces. The study was based on the documental analysis of the referentials of the 3 cycles of EES, of the school reports of the 3rd cycle of EES, and whenever possible, of the reports concerning the same schools in previous cycles of EES. The documental corpus was subjected to content analysis. The results highlight the presence of references to supervision since the 1st cycle of EES and a tendency, particularly in 3rd cycle reports, to value teacher supervision of a collaborative matrix, and to consider that practice is still not fully implemented at schools.